Andropause in Diabetic and Non-diabetic Males: A Cross-Sectional Observational Study in Western India - Kadiwala, Ramiz S; Dhadwad, Jagannath S (Curēus (Palo Alto, CA), 2024)
Andropause is defined as late-onset hypogonadism that increases with advancing age and is diagnosed based on symptoms of hypogonadism like loss of libido, loss of morning penile tumescence, and laboratory confirmation of low testosterone. Unlike menopause, it is a slow and progressive condition with varying symptoms and presentations. There is very little awareness and insufficient utilization of screening methods, and the majority of the cases remain undiagnosed. This study was done to get deeper insight into this topic and elicit correlations among different variables. Objectives The primary objective is to assess the prevalence of andropause in diabetic and non-diabetic males aged 40-60 years in the Maharashtra state of western India. Material and methods After ethics committee clearance, exclusion criteria were applied, and 120 participants were enrolled over a period of 21 months. All enrolled subjects were thoroughly evaluated for andropause symptoms. An early morning venous blood sample was taken and sent for routine blood tests, including HbA1c, serum total testosterone, and serum luteinizing hormone. Total testosterone values were compared in patients with symptoms of hypogonadism, loss of libido, and erectile dysfunction. The effects of HbA1c levels, duration of diabetes, body mass index (BMI), smoking, alcoholism, and hypertension on hypogonadism and low testosterone were assessed. Luteinizing hormone levels were compared among the case and control groups in subjects with low total testosterone. Results Total testosterone levels were low for age, loss of libido and erectile dysfunction were more common, and symptoms of hypogonadism appeared at an earlier age in diabetics compared to non-diabetics. The duration of diabetes and HbA1c had a negative impact on serum testosterone levels and andropause symptoms. Diabetic patients with low testosterone levels had significantly lower LH levels. Conclusions Andropause is a syndrome of hypogonadism that occurs due to low serum testosterone levels. This study puts emphasis on secondary hypogonadism playing an important role in diabetic patients, causing the early occurrence of andropause in them. Glycemic control and BMI have a significant effect on both andropause symptoms and total testosterone levels, necessitating strict glycemic control and lifestyle modifications to delay or prevent the occurrence of andropause.